Character Education for Women: Case Study of Madrasah Muâallimat Muhammadiyah Yogyakarta - MaÃ¢Â€Â™ruf, Syahdara Annisa (Muhammadiyah University Press, 2018)
The present study aims at determining the character education implemented in the intracurricular and extracurricular activities, strategy and expectation for the alumni of Madrasah Muâallimaat Muhammadiyah Yogyakarta in relation with their contribution within family, society and national life. It is a qualitative study by using descriptive method. The findings of this study reveal that the realization of character education in Madrasah Muâallimaat Muhammadiyah Yogyakarta employs holistic approach model. All members of this institution, namely director, dormitory managers, religious teachers, employees, general teacher, students and dormitory staffs should be involved and responsible for the accomplishment of character education. Rules are devised to uphold character values through self-motivation that can be used to instill the character values of the students. They should entail reinforcement, reward and incentive. Madrasah Muâallimaat Muhammadiyah Yogyakarta strives to prepare its graduates with the â3D conceptâ in which the alumni will be ânoticedâ, ârecognizedâ, and âneededâ by the society.